HUMANITARIAN CRISIS IN YEMEN: STUDY OF A SOCIAL SEMIOTIC M.A.K HALLIDAY ON ALJAZEERA.NET NEWS - Luthfiyyah, Nurul; Muassomah, Muassomah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The food and humanitarian crisis in Yemen, caused by prolonged war, has left millions suffering from hunger, disease, and dependence on international aid. Children and women are the most vulnerable groups. This situation is worsened by funding shortages for humanitarian organizations and the impacts of climate change. The research employs a qualitative descriptive method to identify linguistic phenomena within the text by collecting data from books, journals, the internet, and other written literature. The findings, based on M.A.K. Halliday's semiotic theory, reveal that the Al Jazeera news article titled